2019
DOI: 10.2134/agronj2019.03.0174
|View full text |Cite
|
Sign up to set email alerts
|

Horseweed Control with Preplant Herbicides after Mechanical Injury from Small Grain Harvest

Abstract: Horseweed [Conyza canadensis (L.) Cronquist] plants present during small grains harvest are variable in size, but tall plants are mechanically cut (“topped”) by the combine. Horseweed is best controlled prior to planting double‐cropped soybeans, which must be planted quickly after harvest to preserve yield potential. This urgency eliminates an opportunity for horseweed regrowth, leaving topped plants with reduced leaf area for herbicide spray interception, likely impacting herbicidal control, but little inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…This reinforces the need to use different herbicides to control weeds, focusing not only on management, but also on preventing the selection of new resistant biotypes. Other studies demonstrated the effectiveness of these herbicides in the control of species of the genus Conyza [25][26][27][28][29]-in most situations, in combination with other herbicides, including products with confirmed resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This reinforces the need to use different herbicides to control weeds, focusing not only on management, but also on preventing the selection of new resistant biotypes. Other studies demonstrated the effectiveness of these herbicides in the control of species of the genus Conyza [25][26][27][28][29]-in most situations, in combination with other herbicides, including products with confirmed resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the use of herbicides with different mechanisms of action, the combination of herbicides, and the adoption of other tools, in addition to chemical control, are essential in preventing the selection of resistant weed biotypes, as well as in their management (Gage et al, 2019). Studies show the effectiveness of dicamba (Flessner, Pittman, 2019), halauxifen (Krenchinski et al, 2019), glufosinate (Tahmasebi et al, 2018;Zobiole et al, 2018), saflufenacil (Budd et al, 2017), diclosulam (Braz et al, 2017, Krenchinski et al, 2019, especially in combinations, in the control of Conyza spp. and that can be used as control options in the cases of resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Paraquat is widely used to control species such as Conyza spp., in Brazil and other countries, during the off-season and in pre-sowing, after the application of glyphosate plus other herbicides (Santos et al, 2015;Zobiole et al, 2018;Cesco et al, 2019;Flessner, Pittman, 2019;Soltani et al, 2020). In recent years, there has been a reduction in the effectiveness of paraquat in controlling Conyza spp.…”
Section: Weed Managementmentioning
confidence: 99%